2014
DOI: 10.1177/0009922814555977
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators of Pediatric Weight Management Among Diverse Families

Abstract: Multiple barriers and facilitators affect weight management among at-risk families, which should be considered in future obesity interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…8,27 Some parents have competing priorities, feel too over-whelmed to adopt a new concern, or express low confidence in controlling the food and behavior environment, including child-rearing by extended family members. 28,35 The new childhood "norm" of excess body weight makes it difficult for parents and youth to know what healthy children look like. 33,36 Although the Institute of Medicine (2005) and the American Academy of Pediatrics (2007) endorsed the term obesity in child BMI percentile determinations, 34,37,38 some of the pediatric literature finds it pejorative or insensitive for family discussions and shows preference for terms such as unhealthy weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,27 Some parents have competing priorities, feel too over-whelmed to adopt a new concern, or express low confidence in controlling the food and behavior environment, including child-rearing by extended family members. 28,35 The new childhood "norm" of excess body weight makes it difficult for parents and youth to know what healthy children look like. 33,36 Although the Institute of Medicine (2005) and the American Academy of Pediatrics (2007) endorsed the term obesity in child BMI percentile determinations, 34,37,38 some of the pediatric literature finds it pejorative or insensitive for family discussions and shows preference for terms such as unhealthy weight.…”
Section: Discussionmentioning
confidence: 99%
“…21,25,28,34,35,44 Most responses to 9 behavioral questions before the intervention (Table 2) suggested high consumption of sweetened beverages and junk food, prolonged screen time, and a television in the child's bedroom. These survey questions set the tone of behavioral messages for the coming Fitwits discussion.…”
Section: Discussionmentioning
confidence: 99%
“…7 Among the many barriers that Latinos face seeking health care, distance is a significant barrier when frequent specialty care visits are warranted. 6,20 Although many tactics have been employed to combat the growing trend of obesity in this clinic, recently there have been higher success rates for decreasing weight and engaging in healthy lifestyle changes by initiating referral to the multidisciplinary pediatric weight management clinic. A commonly expressed barrier described by Latino patients is distance to the weight management clinic.…”
Section: Pediatric Primary Care Clinicmentioning
confidence: 99%
“…5 It is reported that Latino youth have disproportionately poorer health outcomes as a result of obesity. 5,6 The consequences of childhood obesity can have substantial physical, emotional, and economic impact. Frequent outcomes include cardiovascular disease, type 2 diabetes, orthopedic problems, sleep apnea, as well as social and psychological problems, such as stigmatization, discrimination, and poor selfesteem.…”
mentioning
confidence: 99%
See 1 more Smart Citation